The Human-Centered Narrative of Chinese Path to Modernization - Siqi Wu (International Journal of Social Sciences and Public Administration, 2026)
Human beings are the subject of Chinese path to modernization, the emergence and development of which are oriented toward satisfying the diverse needs of the people and realizing their free and comprehensive development. Chinese path to modernization is characterized by rich theoretical connotations and a sound practical pathway, and distinctly embodies a human-centered feature: a vast population highlights subjectivity; common prosperity underscores sociality; coordination of material and spiritual civilization demonstrates comprehensiveness; harmonious coexistence between humanity and nature reflects ecological consciousness; and peaceful development manifests cosmopolitanism. To articulate the people-centered narrative within the discourse system of Chinese path to modernization, it is essential to present China's story from the perspective of the shared values of all humanity, thereby offering an effective pathway for the world to understand China.